Multi-level security model for privacy preserving in the cloud workflow scheduling. (28th July 2021) - Hammed, S. Shahul; Arunkumar, B.
The traditional security provisioning is concentrating on the authentication of all the data that are critical or no critical results in the increase in computational time and cost. Further, the methods of security provisioning focusing on the sensitive data alone, evinced minimisation of the computational cost and time, but were liable to the unauthorised attacks, as the single level of security was not enough due to the evolving counter technologies. So the paper proffers the single level security provisioning of the sensitive data, by providing a multi-level security that uses the multiple number of cryptographic process for the privacy preserving in the cloud workflow scheduling, by allowing the multi-level cryptographic process without affecting the quality of service, the computational cost and time. The proffered method is validated in the work NS-2 to evidence the quality of service and the minimisation in the computational cost and the execution time.